2013
DOI: 10.1002/path.4173
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the X‐linked tumour suppressors BEX1 and LDOC1 in oral squamous cell carcinoma

Abstract: The strong associations between oral squamous cell carcinoma (OSCC) and dietary habits such as alcohol consumption (A), betel quid chewing (B) and cigarette smoking (C) and its predominance in men have been well documented; however, systemic analysis of OSCC is limited. Our study applied high-throughput screening methods to identify causative epigenetic targets in a cohort of men with ABC-associated OSCC. We identified BEX1 and LDOC1 as two epigenetically silenced X-linked tumour suppressors and demonstrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 42 publications
(48 reference statements)
5
104
0
Order By: Relevance
“…4 These data suggest the possibility that the increased expression of GNL3L, particularly in gastric cancer, may be due to the absence of inhibitory activity of LDOC1 owing to promoter hyper-methylation. 22,30 Furthermore, analysis of in vivo expression pattern of GNL3L and LDOC1 in various primary cancers from BioXpress database indicates an inverse correlation (Fig. 11), supporting the notion that the interplay between GNL3L and LDOC1 may be critical for cell growth control.…”
Section: Discussionmentioning
confidence: 79%
“…4 These data suggest the possibility that the increased expression of GNL3L, particularly in gastric cancer, may be due to the absence of inhibitory activity of LDOC1 owing to promoter hyper-methylation. 22,30 Furthermore, analysis of in vivo expression pattern of GNL3L and LDOC1 in various primary cancers from BioXpress database indicates an inverse correlation (Fig. 11), supporting the notion that the interplay between GNL3L and LDOC1 may be critical for cell growth control.…”
Section: Discussionmentioning
confidence: 79%
“…Using an FDR of 5%, and FC >2 as cut-offs, five genes were identified that were common to arm 4 versus arm 2S, and arm 4 versus arm 3S comparisons ( Table 1 ). The up-regulation of the BEX1 ( brain expressed X-linked 1 ) gene under combination therapy was of particular interest, as this encoded protein has been implicated as a tumor-suppressor gene (TSG) in various cellular contexts (33-35). Similarly, neuronal pentraxin-1 ( NPTX1 ), which is also strongly up-regulated in response to the combination therapy, has been described as a potential TSG or biomarker in a variety of cancer types (36-38).…”
Section: Resultsmentioning
confidence: 99%
“…The WTS results for both BEX1 and NPTX1 were confirmed by qRT-PCR in the xenografts from the study, and the induction of BEX1 by the drug combination was also confirmed in IM-sensitive GIST-T1 and IM-resistant GIST430 cell lines, providing cellular models for exploring this finding. Numerous reports in the literature implicate BEX1 and NPTX1 as tumor-suppressor genes or biomarkers in various cancers (33-35,37,38). Both genes have been implicated in connection with pro-apoptotic pathways in different cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of glioma cells with TSA or 5-AzaC resulted in strong induction of BEX1 and BEX2 expression suggesting an epigenetic suppression of its expression in glioma which was further shown to be mediated through promoter methylation and histone modification [52]. Methylation of the BEX1 promoter was associated significantly (p < 0.0001) with oral squamous cell carcinoma (OSCC) and were detected in 75% (42/56) of the samples [53]. TSA and 5-AzaC treatment substantially elevated BEX2 expression in MLL wild-type AML cells suggesting that BEX2 is epigenetically suppressed in AML as well [23].…”
Section: Epigenetic Suppression Of Bex Expressionmentioning
confidence: 99%